Evaluasi Kualitas dan Kesuksesan Implementasi E-Learning Fakultas Ilmu Komputer Menggunakan Model Unified Theory of Acceptance And Use Of Technology, Model Delone & Mclean dan Hot Fit Terintegrasi - Bayu Andhika Sarwono; Retno Indah Rokhmawati; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Based on data obtained from observations at the Faculty of Computer Science (FILKOM) in Universitas Brawijaya who have made use e-learning. This study aims to determine the quality conditions and the success of e-learning implementation. This study uses an integrated evaluation model from the acceptance model of the Unified Theory Acceptance and Use of Technology (UTAUT), the success information system model of DeLone & McLean and the HOT Fit human-organization-technology conformity model integrated with modifications adapted to the characteristics of the Faculty of Computer Science and can describe the success and acceptance of e-learning itself. The used data in this study were obtained from 100 respondents using purposive sampling technique. Data collection is done through a questionnaire. Data analysis in this study used descriptive statistical methods. The results show that Social influence variables, service quality, user satisfaction, Top Management Support, and Organization support into the high enough category and other variables enter the high category. The recommendations from this study are based on indicators of each variable which has a value below the total average so that later it can improve the quality and success of e-learning implementation.